Contributions to the wetlands supplement of the IPCC Guidelines for National Greenhouse Gas Inventories - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
The 2006 Intergovernmental Panel on Climate Change (IPCC) Guidelines for National Greenhouse Gas Inventories provide countries with methodologies for estimating national inventories of emissions by sources and sinks. However, until recently, there was a lack of sufficient data concerning the carbon stocks of wetlands and peatlands. These valuable forest ecosystems are rich in carbon, meaning that improper management practices can be extremely costly in terms of greenhouse gas emissions. If these ecosystems are absent from estimations, it can be difficult for policymakers to holistically assess and plan their greenhouse gas inventories and mitigation strategies.